Zostań MovieStarPlanet! – czyli o partycypacji kultury dziecięcej w kulturze cyfrowej - Joanna Dziekońska (Problemy Wczesnej Edukacji)
This article reflects on the specificity of contemporary children’s participation in digital culture. It comprises study results, whose aim was the reconstruction of children’s culture created by children during internet communication in the MovieStarPlanet service. The communication in the service has been treated as an example of a new dimension of children’s culture and, as such, it is the subject of the present study. The adopted study procedure mainly comprised the netnographic method and revealed many original examples of children’s culture. Among the creations published by children in the service, the following were distinguished, among others, multimedia images (ArtBooks, arts), several short audio-visual pieces, animated photos, stylings (looks) as well as text thematic games published on the forum. The analysis of children’s e-folklore allowed formulating conclusions on the communal and creative functioning of children in a selected web place, a rich variety of themes and types of undertaken communication initiatives and the existence of specific features of children’s language suggesting the existence of the internet aspect of children’s culture.